Programming fitness-program for senior pupils to do physical exercises independently - Vashchuk, Ludmyla (Journal of Education, Health and Sport, 2017)
Vashchuk Ludmyla. Programming fitness-program for senior pupils to do physical exercises independently. Journal of Education, Health and Sport. 2016;6(11):368-382. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.168092 http://ojs.ukw.edu.pl/index.php/johs/article/view/4009 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.11.2016. Revised 12.11.2016. Accepted: 23.11.2016. Programming fitness-program for senior pupils to do physical exercises independently Ludmyla Vashchuk Lesya Ukrainka Eastern European National University (Lutsk, Ukraine) Fitness-program is characterized by the set of the specially selected physical exercises aimed at the complex or selective impact on the body or some parts of the body depending on the morpho-functional human capacity. Introduced general structure of the fitness-program may be corrected depending on the targets of the training, physical state and senior pupils’ motivation. Some fitness-programs containing muscle-strengthening exercises were introduced to solve the problems of the correction of the body. The muscle-strengthening exercises for increasing the body weight, circumference of the parts of the body (shoulders, chest, pelvis, thighs), improving the rates of muscle tonus were recommended for the girls having asthenic body build. The senior pupils having hypersthenic body build did exercises to decrease the body weight and circumference of the parts of the body (shoulders, breast, pelvis, thighs), fatty component. The physical exercises for a normosthenic body build were aimed at amelioration of muscle tonus, decreasing the rate of the increase of body weight and circumference of pelvis. Keywords: fitness-programs, senior pupils, programming, physical exercises, correction of body build.